2016
DOI: 10.1101/gr.210930.116
|View full text |Cite
|
Sign up to set email alerts
|

Enhancers and super-enhancers have an equivalent regulatory role in embryonic stem cells through regulation of single or multiple genes

Abstract: Transcriptional enhancers are critical for maintaining cell-type-specific gene expression and driving cell fate changes during development. Highly transcribed genes are often associated with a cluster of individual enhancers such as those found in locus control regions. Recently, these have been termed stretch enhancers or super-enhancers, which have been predicted to regulate critical cell identity genes. We employed a CRISPR/Cas9-mediated deletion approach to study the function of several enhancer clusters (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
175
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(184 citation statements)
references
References 109 publications
(135 reference statements)
8
175
0
1
Order By: Relevance
“…In contrast, the Esrrb enhancer (Festuccia et al , 2012; Moorthy et al , 2017), which is active in ESCs but inactive in primed pluripotent cells, becomes completely methylated as cells commit to differentiate. Our results build on previous reports that accumulation of DNA methylation at the regulatory regions of pluripotency genes accompanies loss of naïve pluripotency (Ficz et al , 2013; Habibi et al , 2013; Hackett et al , 2013; Leitch et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Esrrb enhancer (Festuccia et al , 2012; Moorthy et al , 2017), which is active in ESCs but inactive in primed pluripotent cells, becomes completely methylated as cells commit to differentiate. Our results build on previous reports that accumulation of DNA methylation at the regulatory regions of pluripotency genes accompanies loss of naïve pluripotency (Ficz et al , 2013; Habibi et al , 2013; Hackett et al , 2013; Leitch et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We examined whether super-enhancers and enhancers exhibit structural variations in 3D genome maps. To this end, we selected a list of candidates whose enhancer function has been validated (22). Both super-enhancers and enhancers are linked to their promoter by similar architectural stripes, with no significant difference between them in terms of chromatin conformation and interaction intensity.…”
Section: Stripe Decaying Curve Analysismentioning
confidence: 99%
“…An additional concern is the "stitching" step of super-enhancer analysis, in which putative enhancer regions located within a specific distance of each other (the default in the ROSE algorithm is 12.5 kb, and so this is most often used) are considered as a single element, under the assumption that closely-spaced enhancers work together in activation of the same gene or genes [6][7][8] . Some studies have questioned the general validity of this assumption 10,31 , and our own analysis of the Tspan32 locus presents a clear example of how the superenhancer concept tends to oversimplify more complex patterns of gene regulation. We found that the Tspan32 super-enhancer, comprised of three distinct candidate enhancer regions, is in fact involved in the regulation of two additional genes as well as Tspan32.…”
Section: Discussionmentioning
confidence: 97%